Analisis Wanprestasi Terhadap Perjanjian Jual Beli Tanah Secara Lisan: (Studi Kasus Pada Perkara Nomor 40/Pdt.G/2019/PN Kdi) - Adinda Aristias; Hanifah Fairuz Wibowo; Nasywa Awalia Putri; Tyur Reggina Dewanti; Syaiful Malik; Dwi Aryanti Ramadhani (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Humans are social creatures, so they need help from other people in carrying out their lives. In establishing a legal relationship with another human being, a binding agreement is required as regulated in the Civil Code Book III concerning engagement. The agreement can be made in writing or verbally and contains a clause to carry out an achievement. However, the agreement also does not guarantee that no default will occur, as in case number 40/Pdt.G/2019/PN Kdi related to default that occurred in an oral agreement. This research aims to determine the validity of oral land sale and purchase agreements and evidence in resolving defaults on oral agreements in case Number 40/Pdt.G/2019/PN Kdi. This research method is normative law which is descriptive analysis by examining theories, concepts, principles and legal rules contained in books, journals, websites, statutory regulations, court decisions, legal theories and opinions from experts. Oral agreements can be used and are legally valid with the principle of freedom of contract and when Article 1320 of the Civil Code has been fulfilled. Then, the case of breach of verbal agreement in case Number 40/Pdt.G/2019/PN Kdi was resolved with evidence which included evidence and witness statements which were taken into consideration by the judge in deciding the case.